Hypertriglyceridemia in an outpatient department – Significance as an atherosclerotic risk factor. (May 2015) - Scholz, M.; Tselmin, S.; Fischer, S.; Julius, U.
Abstract: Background: Although a relationship between elevated triglycerides (TG) and cardiovascular diseases is generally accepted, its extent is still discussed. This retrospective study analyzed the incidence of cardiovascular events (CVE) and pancreatitis as well as the therapeutic regimen in patients being treated for hypertriglyceridemia (HTG) at an outpatient department. Methods: The cohort included 183 patients with mild and 49 patients with severe HTG; subgroups were formed and compared according to gender, presence of metabolic vascular syndrome (MVS) and lipid values. Results: Patients in this study seem to have had CVE at younger age than reported event rates in the general population. TG levels, rates of CVE and pancreatitis were reduced in all groups during therapy, which could be linked to use of omega-3 fatty acids and fibrates. Patients with persisting severe HTG as a result of incompliance showed massive risk for pancreatitis. Conclusion: Although no significant association between TG levels and CVE could be established, the combination of HTG and other cardiovascular risk factors such as MVS seems to be especially dangerous. The lipid-lowering drug therapy appeared to be effective with respect to CVE and pancreatitis incidence.